Characterization and clinical evaluation of microsatellite instability and loss of heterozygosity within tumor-related genes in colorectal cancer - Xueyun Huo; Dandan Feng; Shuangyue Zhang; Zhenkun Li; Xiaohong Li; Changlong Li; Meng Guo; Jin Wang; Zhongtao Zhang; Qingxian Lu; Xiaoyan Du; Zhigang Bai; et al. (BMC, 2021)
Abstract Background Microsatellite instability (MSI) is a biomarker for better outcomes in colorectal cancer (CRC). However, this conclusion is controversial. In addition, MSs can be a useful marker for loss of heterozygosity (LOH) of genes, but this finding has not been well studied. Here, we aimed to clarify the predictive value of MSI/LOH within tumor-related genes in CRC. Methods We detected MSI/LOH of MSs in tumor-related genes and the Bethesda (B5) panel by STR scanning and cloning/sequencing. We further analyzed the relationship between MSI/LOH status and clinical features or outcomes by Pearson's Chi-square test, Fisher's exact test and the Kaplan-Meier method. Results The findings indicated that the MSI rates of B5 loci were all higher than those of loci in tumor-related genes. Interestingly, MSI/LOH of 2 loci in the B5 panel and 12 loci in tumor-related genes were associated with poorer outcomes, while MSI/LOH of the B5 panel failed to predict outcomes in CRC. MSI of BAT25, MSI/LOH of BAT26 and MSI of the B5 panel showed closer relationships with mucinous carcinoma. In addition, LOH-H of the B5 panel was associated with increased lymphatic metastasis. Conclusions In summary, MSI/LOH of certain loci or the whole panel of B5 is related to clinical features, and several loci within tumor-related genes showed prognostic value in the outcomes of CRC.